2014
DOI: 10.1128/jcm.02121-14
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Detection of Carbapenemase-Producing Enterobacteriaceae by Use of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry and the Carba NP Test

Abstract: f We compared the diagnostic accuracy of the Carba NP test with that of a straightforward matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) method for detecting carbapenemase-producing Enterobacteriaceae (CPE). Using PCR as the reference method, both tests demonstrated a sensitivity of 87% and a specificity of 100%. MALDI-TOF MS offers a potential alternative for the rapid detection of CPE in the clinical laboratory setting. The global spread of carbapenemase-producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 14 publications
(6 reference statements)
1
24
1
5
Order By: Relevance
“…Our results showed slight difference from those of Knox and his colleagues (2014) in Australia who evaluated the performance of Carba NP test in detecting carbapenemase production by Enterobacteriaceae in comparison to PCR and found that the sensitivity and specificity of the Carba NP test were (40/46) 87% and (59/59) 100% respectively (19) .…”
Section: Chromagar Kpccontrasting
confidence: 96%
“…Our results showed slight difference from those of Knox and his colleagues (2014) in Australia who evaluated the performance of Carba NP test in detecting carbapenemase production by Enterobacteriaceae in comparison to PCR and found that the sensitivity and specificity of the Carba NP test were (40/46) 87% and (59/59) 100% respectively (19) .…”
Section: Chromagar Kpccontrasting
confidence: 96%
“…inexpensive test to detect carbapenemase activity (Nordmann et al, 2012b;Dortet et al, 2012), but the use of MALDI-TOF MS for carbapenemase detection has been increasing (Hrabak et al, 2011(Hrabak et al, , 2012Kempf et al, 2012;Wang et al, 2013;Sauget et al, 2014;Johansson et al, 2014;Hoyos-Mallecot et al, 2014;Nagy et al, 2014;Knox et al, 2014;Hrabak, 2015). In this report, we used MALDI-TOF MS analysis to detect carbapenemase activity in a diverse panel of clinical isolates of Enterobacteriaceae spp., P. aeruginosa and A. baumannii that collectively express one of eight different carbapenemases, and compared the results against the use of the Carba-NP assay on selected isolates.…”
mentioning
confidence: 96%
“…Most studies have evaluated ertapenem hydrolysis by testing the Microflex LT instrument (Bruker Daltonics) (Carvalhaes et al, 2013). To the best of our knowledge, only one recently published study evaluated the detection of carbapenemase activity by using the VITEK MS instrument (bioMérieux) (Knox et al, 2014). The authors reported a lack of sensitivity (87 %) by testing imipenem as substrate.…”
mentioning
confidence: 99%